PENGARUH AKTIVA PAJAK TANGGUHAN DAN BEBAN PAJAK KINI DALAM MENDETEKSI INCOME MAXIMIZATION - Revy Wilhelmina Silooy (Soso-Q : Jurnal Manajemen, 2017)
This study aims to prove the effect of deferred tax assets and current tax expense in detecting income maximization when seasoned equity offeringsData obtained from the results of data collection of financial statements of companies listed on the stock exchange of Indonesia from 2005-2014 with a total sample of 30 companies.The results show that the deferred tax assets and the current tax burden have a significant effect in detecting income maximization when the company does seasoned equity offering activities. This is because each company has a target achievement of earnings management and strives to achieve high revenue targets, thus encouraging the company to conduct stock offering activities in order to obtain profits as much as possible. Keywords : tax, income maximization, seasoned equity offerings.